Targeting Mitochondrial Metabolism and RNA Polymerase POLRMT to Overcome Multidrug Resistance in Cancer - Yu, Hui-Jing; Xiao, Guan-Li; Zhao, Yu-Ying; Wang, Xin-Xin; Lan, Rongfeng (Frontiers in Chemistry, 2021)
Clinically, the prognosis of tumor therapy is fundamentally affected by multidrug resistance (MDR), which is primarily a result of enhanced drug efflux mediated by channels in the membrane that reduce drug accumulation in tumor cells. How to restore the sensitivity of tumor cells to chemotherapy is an ongoing and pressing clinical issue. There is a prevailing view that tumor cells turn to glycolysis for energy supply due to hypoxia. However, studies have shown that mitochondria also play crucial roles, such as providing intermediates for biosynthesis through the tricarboxylic acid (TCA) cycle and a plenty of ATP to fuel cells through the complete breakdown of organic matter by oxidative phosphorylation (OXPHOS). High OXPHOS have been found in some tumors, particularly in cancer stem cells (CSCs), which possess increased mitochondria mass and may be depends on OXPHOS for energy supply. Therefore, they are sensitive to inhibitors of mitochondrial metabolism. In view of this, we should consider mitochondrial metabolism when developing drugs to overcome MDR, where mitochondrial RNA polymerase (POLRMT) would be the focus, as it is responsible for mitochondrial gene expression. Inhibition of POLRMT could disrupt mitochondrial metabolism at its source, causing an energy crisis and ultimately eradicating tumor cells. In addition, it may restore the energy supply of MDR cells to glycolysis and re-sensitize them to conventional chemotherapy. Furthermore, we discuss the rationale and strategies for designing new therapeutic molecules for MDR cancers by targeting POLRMT.